2020
DOI: 10.1177/1756284820968736
|View full text |Cite
|
Sign up to set email alerts
|

Empirical or susceptibility-guided treatment forHelicobacter pyloriinfection? A comprehensive review

Abstract: Although susceptibility-guided therapy is frequently recommended for Helicobacter pylori infection, the evidence available to date supporting this strategy is limited. The aim of the present article is to review the advantages and limitations of the susceptibility-guided and the empirical strategies to treat this infection. We performed a bibliographic search to identify studies investigating H. pylori susceptibility-guided therapy. Culture is not the only way to assess antibiotic resistance, as different poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 121 publications
(224 reference statements)
0
63
0
6
Order By: Relevance
“…Furthermore, H. pylori has slow bacterial growth and particular nutritional requirements, and culture-based methods are time-consuming (10 to 15 days), expensive, technically challenging, susceptible to inter-observer variability, and are not able to detect hetero-resistance status [ 11 ]. For these reasons, even tailored regimens were found to be no better than empiric therapies [ 51 ]. Therefore, standard therapies are empirically administered for H. pylori infection retreatment in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, H. pylori has slow bacterial growth and particular nutritional requirements, and culture-based methods are time-consuming (10 to 15 days), expensive, technically challenging, susceptible to inter-observer variability, and are not able to detect hetero-resistance status [ 11 ]. For these reasons, even tailored regimens were found to be no better than empiric therapies [ 51 ]. Therefore, standard therapies are empirically administered for H. pylori infection retreatment in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, in some cases, H. pylori infection persists even after two or more eradication treatments, and these patients constitute a therapeutic dilemma. Currently, a standard third/fourth-line therapy is lacking, and international guidelines recommend performing culture in these patients to select a rescue treatment according to microbial sensitivity to antibiotics, but this strategy is not practical [ 14 ]. Therefore, the evaluation of drugs without cross-resistance to macrolides, nitroimidazole or quinolones as components of retreatment combination therapies seems to be worthwhile [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gweon et al showed that the cost for a successful eradication using DPObased PCR would be similar or superior to the expected cost of a successful eradication with a 14-day empirical treatment when the first-line eradication rate is ≤80% [29]. Since H. pylori antibiotic resistance varies among different geographic areas, the cost-effectiveness may vary according to the cost of care in a given country, and therefore the same conclusion may not be applicable to other healthcare systems [30].…”
Section: Discussionmentioning
confidence: 99%